Cloud Education: Aprendizagem Colaborativa em Nuvem através do Kindle e de Redes Sociais - Mansur, Andre F. Uebe; Gomes, Elizabeth L.; Carvalho, Rogério A. de; Biazus, Maria Cristina V. (Cadernos de Informática, 2011)
This paper is part of an initial doctoral research which focuses on an alternative teaching approach for Trainee Programs in undergraduate courses in Business. Through this new approach, concepts like Social Networking and Cloud Education are used to promote collaborative learning, by providing better interaction among students in a trainee program. The methodology proposes to use Kindle, an Amazon Cloud Library access gadget, as a collaborative learning interface to improve the absorption of theoretical knowledge by the students.